Lockdown Measures Against the Spread of the COVID-19 Pandemic: Negative Effects for People Living With Depression - Czaplicki, Andreas; Reich, Hanna; Hegerl, Ulrich (Frontiers in Psychology, 2022)
The COVID-19 pandemic and associated measures to restrict the spread of the virus correlated with limitations in healthcare and changes in depression-related lifestyle elements (loss of daily structure, lack of exercise, and extended bed and sleep time) for depressed patients, both of which are known to negatively affect the course of depression. This paper examines, (i) the reporting of a worsening state of illness as a result of COVID-19-related measures among individuals with depressive disorders; and (ii) whether this worsening was related to restrictions in healthcare for depression or changes in depression-related lifestyle. The analysis was based on a population-representative survey of the German population aged 18–69 years (N = 5,135 respondents, comprising a subgroup of n = 1,038 persons suffering from depression and n = 598 persons who spent the lockdown primarily in home isolation). The key findings were: 49% (n = 505) of respondents with self-reported diagnosed depression reported that the measures against the pandemic had a negative impact on their depressive illness (new depressive episode, worsening of symptoms, suicidal impulses, suicide attempt, and other negative consequences). Of those who reported impaired access to healthcare for their depressive illness, 70% (n = 276) also reported a worsening of their depressive illness. This was a significantly higher percentage than those who did not experience impaired access to healthcare (36%, n = 229, p < 0.001). Of those who reported changes in depression-related lifestyle (loss of daily structure, lack of exercise, or extended bed and sleep time), 58% (n = 308) reported a worsening of their depressive illness. This was a significantly higher percentage than those who did not exhibit any of the outlined behaviours (28%, n = 19, p < 0.001). Worsening of the depressive illness was most common among those who reported a lack of daily structure or extended bedtimes (67%; n = 230 resp. N = 226). People who mentioned a lack of exercise also reported a worsening of their depressive illness (59%; n = 271). These findings reinforce the need to consider the suffering and possible increased suicide risk to people suffering from depression induced by measures designed to constrain the COVID-19 pandemic; an important consideration in identifying the optimal risk-benefit ratio when setting pandemic measures. Our study highlighted the importance of maintaining healthcare, even in crisis situations, and ensuring access to guideline-based treatment for people who need urgent care. It also showed that political interventions can influence individual behaviours that can have negative effects on depressive illness.